Management Of Labor Standardization System Assessment Processes In Small Business Enterprises - Abdukhamidov, Abdurakhmon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This scientific work analyzes the main structural elements of the labor standardization system in small enterprises and their functional significance. Modern mechanisms of labor standardization, standards of time, service, volume of work in production processes, organization of the workplace, and normative bases of labor actions are determined. The study studies methods for assessing the effectiveness of the standardization system - expert assessment, index of indicators, technological time analysis and evaluation mechanisms based on complex labor efficiency indicators.